Procedura regionalnych badań segmentacyjnych - Sobczak, Elżbieta (The Procedure for Regional Segmentation Research, 2008)
The objective of the study is to present the procedure for regional segmentation research carried out within international space. The procedure is of multi-level nature and consists of follow-up stages covering the research concept, its realization, the communication of results and their application. The scope of segmentation research is influenced by the selection of regional segmentation variant, the researched unit and the segmentation model. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 239-246